Ventriculoperitoneal Shunt Infection: A Study about Age as a Risk Factor in Hydrocephalus Pediatrics - Bastian, Reza Akbar (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: Shunt infection is one of the dreaded and serious complications following ventriculoperitoneal shunt (VP shunt) insertion, especially in a pediatric population. Numerous risk factors have been identified, particularly in developing countries, indicating that age may play an essential element in the pathogenesis of shunt infection, typically in patients <1-year-old. However, a few research demonstrate the inverse result. AIM: The purpose of this was to determine the relationship between age and shunt infection so that it can be taken into consideration when performing VP shunt insertion. METHODS: From January 2017 to December 2019, 98 pediatric patients with hydrocephalus who underwent VP shunt insertion were retrospectively reviewed to determine the relationship between age and shunt infection. We evaluated the microbiology results and management of shunt infection in patients with shunt infection. RESULTS: Fifteen (15.15) of 98 patients developed shunt infection. Patients aged >3–6 months had a significantly increased risk of shunt infection (p = 0.04; RR = 4.15; CI 95 = 1.19–14.45). Staphylococcus aureus was the most frequently encountered pathogen in pediatric patients with shunt infection (53.3), and the most common management for shunt infection was complete removal of the shunt and systemic antibiotics followed by re-insertion of the shunt after the cerebrospinal fluid was sterile (46.6). CONCLUSION: We conclude that age, especially those aged >3–6 months, has a significantly higher risk of shunt infection in pediatric patients. © 2022 Reza Akbar Bastian, Handoyo Pramusinto, Endro Basuki, Marianne Marianne.